A Novel AC Green Plug Switched Filter Scheme for Low Impact Efficient V2G Battery Charging Stations - Albe M. Bloul; Adel M. Sharaf; Hamed H. Aly; Jason Gu (International Transactions on Electrical Energy Systems)
In this paper, a novel switched/modulated capacitor filter scheme is proposed for enhancing vehicle-to-house (V2G) battery-charging stations utilized in electric vehicles (EVs). The novel approach is tested on two controllers with a classical optimized PID controller. The technique, which employs modified multimode weighted charging modes for fast charging, improved power quality, and minimal inrush currents, results in reduced voltage transients on the DC side and less harmonics on the AC side. An intercoupled DC-AC capacitor interface that features dual complementary switching modes is used by the switched modulated filter as a way to provide optimal pulsing in both the tuned-arm filter and capacitive compensator modes of operations. This switched intercoupled AC-DC filter compensation approach leads to enhanced power usage in EVs, along with lower AC-DC voltage transients and inrush currents.